Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1038/330041a0
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of hydrogen bonds of Thr 157 to the thermodynamic stability of phage T4 lysozyme

Abstract: Measurements of changes in structure and stability caused by 13 different substitutions for threonine 157 in phage T4 lysozyme show that the most stable lysozyme variants contain hydrogen bonds analogous to those in the wild-type enzyme and that structural adjustments allow the protein to be surprisingly tolerant of amino-acid substitutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 295 publications
(141 citation statements)
references
References 0 publications
5
134
1
Order By: Relevance
“…I47 A between the structures (Table 2). This interaction resembles one seen in the structure of a T157G mutant of T4 lysozyme (Alber et al, 1987;Matthews, 1993), where an ordered water molecule, acting as a surrogate for the missing T157 hydroxyl, preserves the pattern of stabilizing hydrogen bonding interactions seen in the native protein. It is interesting that, in spite of the high degree of conservation seen in the structure of the R42I mutant complex, CN inhibition is nonetheless reduced by -180-fold ( Table I).…”
Section: S Itoh and M A Naviamentioning
confidence: 62%
“…I47 A between the structures (Table 2). This interaction resembles one seen in the structure of a T157G mutant of T4 lysozyme (Alber et al, 1987;Matthews, 1993), where an ordered water molecule, acting as a surrogate for the missing T157 hydroxyl, preserves the pattern of stabilizing hydrogen bonding interactions seen in the native protein. It is interesting that, in spite of the high degree of conservation seen in the structure of the R42I mutant complex, CN inhibition is nonetheless reduced by -180-fold ( Table I).…”
Section: S Itoh and M A Naviamentioning
confidence: 62%
“…Zhang and Matthews (1994) observed that those most conserved are frequently internal and are characterized by low crystallographic thermal factors. It has been suggested that well-ordered, internal water molecules are significant factors in determining structural stability (Alber et al, 1987;Williams et al, 1994) or function (Alexander et al, 1991;Meyer, 1992). The subject has been reviewed by Westhof (1993) and by Teeter (1991).…”
Section: Conserved Buried Water Molecules In the Lysozyme Corementioning
confidence: 99%
“…Studies of T4 lysozyme mutants have suggested that mutations that remove hydrogen-bonding residues are less destabilizing if the replacements are small residues that allow room for a hydrogen-bonding water molecule to be positioned at the site of the mutation (Alber et al, 1987). Therefore, it is interesting to compare the stability of N43G to those of mutations in which Asn 43 is replaced by a bulkier residue.…”
Section: Hydrogen Bondsmentioning
confidence: 99%